AN ATTEMPT TO A CONTRASTIVE ANALYSIS OF IGBO AND TONGAN CONDITIONAL CLAUSES - Güçlü, Ruhan (PEOPLE: International Journal of Social Sciences, 2020)
This study examines the conditional sentence structures in Igbo and Tongan languages and aims to reveal the similarities and differences between these languages regarding the semantic structure and syntactic characteristics of the conditional clauses. Therefore, the contrastive analysis procedure is applied which consists of three steps as (1) description; (2) juxtaposition; (3) comparison (Krzeszowski, 1990). In pursuit of the description of the conditional sentence structures in Igbo and Tongan languages, they are juxtaposed and compared. This contrastive analysis procedure revealed that Igbo and Tongan languages have both the first, second, and third conditions. In addition, Tongan has also zero conditions. Moreover, they may use different forms to express the condition which gives the meaning that the situation may or may not be fulfilled, theoretically possible but unlikely future situations and impossible conditions. In view of all the similarities and differences found in the analysis, Tongan and Igbo languages which are the member of different language families and whose native speakers live so far away from each other share common points in regard to the types of conditional clause while their structures differ in terms of degree.